Student' speaking problem in English daily language program at one islamic boarding school in Majalengka - nur alim, mohamad (Papanda Publisher, 2023)
This study aims to determine the problem of speaking in one Islamic boarding school in Majalengka. The purpose of this study is to find students' problems in learning English speaking skills. The design of this study uses a qualitative descriptive method. The subjects of this study were class lX students of At-tadzkir Islamic Boarding School. The research data was collected using observation, interviews, and documentation. From the findings and discussions, students have problems in speaking. These problems consist of shyness, grammar, vocabulary and meaning, pronunciation, lack of confidence, fear of making mistakes, and anxiety. From the dominant problem is the problem of pronunciation. Most of them stated that they were afraid to speak because they did not know how much vocabulary and how to pronounce the words. They are afraid if they make mistakes in terms of pronunciation and use of vocabulary.